Differential effects on innate versus adaptive immune responses by WF10 - Giese, Thomas; McGrath, Michael S.; Stumm, Susanne; Schempp, Harald; Elstner, Erich; Meuer, Stefan (Cellular immunology, 2004)
Oxidative compounds that are physiologically generated in vivo can induce natural defense mechanisms to enhance the elimination of pathogens and to limit inflammatory tissue damage in the course of inflammation. Here, we have investigated WF10, a chlorite-based non-toxic compound for its functional activities on human PBMC in vitro. WF10 exerts potent immune-modulatory effects through generating endogenous oxidative compounds such as taurine chloramine. Proliferation and IL-2 production of anti-CD3 stimulated PBMC were inhibited by WF10, as was the nuclear translocation of the transcription factor NFATc. In PBMC and monocytes, however, WF10 induced pro-inflammatory cytokines like IL-1beta, IL-8, and TNF-alpha. In the monocytic cell line THP-1, the activation of the transcription factors AP-1 and NFkappaB by WF10 was demonstrated. Inhibition of NFAT regulated genes in activated lymphocytes in concert with the induction of several myeloid cell associated pro-inflammatory genes in monocytes represents a novel mechanism of immune modulation.
Gesehen am 14.06.2021